Hambatan Pedagang Ayam Potong Di Pasar Babat Lamongan Dalam Melakukan Sertifikasi Halal - Klarista Mayang Sari; Aries Kurniawan; Vembri Aulia Rahmi; Hadi Ismanto (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2023)
The implementation of halal certification for broiler traders at the Babat Lamongan Traditional Market has not run optimally, as evidenced by the fact that many broiler traders do not yet have halal certification. There are several reasons why the broiler traders at the Babat Lamongan Traditional Market do not have halal certification. The purpose of this study is to find out what obstacles the chicken traders experience at the Babat Lamongan Traditional Market so that they do not have halal certification. This study uses a qualitative research method with a descriptive approach. The results of this study are that the broiler traders at Babat Lamongan Traditional Market do not yet have halal certification due to five factors namely, economy, mindset, administration, technology and knowledge.